Coating liquid and projection formation method

A coating liquid with specific solvent and particle ratios forms a coating layer with strong and uniform protrusions, enhancing the capture efficiency of biological samples by increasing surface area and adherence.

JP2024176755APending Publication Date: 2024-12-19TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023095536
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing technologies face challenges in forming protrusions with high strength and uniformity on coating layers for efficient capture of biological samples such as cells and extracellular vesicles.

Method used

A coating liquid comprising irregularly shaped particles, a polymer, a poor solvent, and a good solvent with specific volume ratios and boiling point differences is used to form a coating layer with protrusions, where the irregularly shaped particles are partially buried and partially exposed, enhancing strength and uniformity.

Benefits of technology

The method achieves a coating layer with highly uniform and strong protrusions, improving the capture efficiency of biological samples by increasing the surface area and adherence of particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176755000002
    Figure 2024176755000002
  • Figure 2024176755000003
    Figure 2024176755000003
  • Figure 2024176755000004
    Figure 2024176755000004
Patent Text Reader

Abstract

To provide a coating liquid capable of forming a coating layer with projections having high strength disposed at high uniformity.SOLUTION: A coating liquid includes: (1) irregular shape particles; (2) polymer; (3) a poor solvent of the polymer; and (4) a good solvent of the polymer, the good solvent having a lower boiling point than that of the poor solvent. A ratio of a volume of the component (1) to a volume of the component (2) is 1 / 4 to 10 / 1. A ratio of the volume of the component (1) to a sum total of the volume of the component (2) and the volume of the component (3) is 1 / 10 to 1 / 2. A ratio of a volume of the component (4) to the volume of the component (3) is 1 / 1 to 100 / 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating liquid and a method for forming protrusions. [Background technology]

[0002] Attempts to imitate the excellent functions of living organisms are called biomimetics, and a typical example is the development of functions that mimic the uneven structures present on the surfaces of living organisms and plants. For example, an anti-reflective coating has been proposed that reduces reflectance by forming a protrusion structure similar to that of a moth's eyes on the surface of a film. This anti-reflective coating utilizes the fact that the spatial occupancy rate of the uneven structure on the surface changes continuously from the air interface to the substrate side, forming a refractive index gradient structure in which the effective refractive index changes continuously from the air interface to the substrate side, eliminating the reflective interface and preventing reflection. In addition, it is known that the protrusions with a hierarchical structure present on the surface of lotus leaves exhibit super-water repellency with a water contact angle of more than 150°.

[0003] As an example of an article having such a fine uneven structure, Patent Document 1 discloses an anti-reflective article having a specific fine uneven structure on its surface. Patent Document 2 discloses a chip for extracting biomolecules, which includes a substrate, a microchannel formed on the substrate, and a nanowire formed in the microchannel, with a part of the nanowire embedded in the microchannel. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-209540 A [Patent Document 2] Patent No. 6606786 Summary of the Invention [Problem to be solved by the invention]

[0005] It is believed that a device having a coating layer with a fine uneven structure, in which protrusions are provided on at least a part of the surface, can capture biological samples such as cells, extracellular vesicles, proteins, etc. From the standpoint of the efficiency of capturing a target component in a biological sample, it is desirable that protrusions with high strength are formed with high uniformity on the coating layer.

[0006] An object of the present invention is to provide a coating liquid capable of forming a coating layer on which protrusions exhibiting high strength are provided with high uniformity, and a method of forming protrusions using the coating liquid. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have found that the above problems can be solved by a coating liquid containing irregularly shaped particles, a polymer, a poor solvent for the polymer, and a good solvent for the polymer having a boiling point lower than that of the poor solvent in specific proportions, thereby completing the present invention.

[0008] That is, the respective aspects of the present invention are [1] to [7] shown below. [1] A coating liquid comprising: (1) irregularly shaped particles; (2) a polymer; (3) a poor solvent for the polymer; and (4) a good solvent for the polymer, the good solvent having a boiling point lower than that of the poor solvent, wherein the ratio of the volume of the component (1) to the volume of the component (2) is 1 / 4 to 10 / 1; the ratio of the volume of the component (1) to the total volume of the component (2) and the component (3) is 1 / 10 to 1 / 2; and the ratio of the volume of the component (4) to the volume of the component (3) is 1 / 1 to 100 / 1. [2] The coating liquid according to [1], wherein the irregular-shaped particles have a major axis of 0.1 to 100 μm, a minor axis of 0.01 to 10 μm, and a ratio of the major axis of the irregular-shaped particles to the minor axis of the irregular-shaped particles is 2.0 or more. [3] The coating liquid according to [1] or [2], wherein the poor solvent has a fluorine group. [4] The coating liquid according to any one of [1] to [3], wherein the poor solvent has a boiling point of 200° C. or lower under atmospheric pressure. [5] The coating liquid according to any one of [1] to [4], wherein the poor solvent has a surface tension of 22 mN / m or less. [6] The coating liquid according to any one of [1] to [5], wherein the irregularly shaped particles are surface-modified with a silane coupling agent having a (meth)acryloyl group, and the difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer is 5 or less. [7] A method for forming protrusions, comprising the following steps [1] to [3]: [1] A step of applying the coating liquid according to any one of [1] to [6] to a supporting substrate to form a coating film. [2] A step of volatilizing the good solvent from the coating film to insolubilize the polymer [3] A step of volatilizing the poor solvent from the coating film in which the polymer has been insolubilized. Effect of the Invention

[0009] According to the present invention, it is possible to provide a coating liquid capable of forming a coating layer on which protrusions exhibiting high strength are provided with high uniformity. According to the present invention, it is possible to provide a method for forming protrusions using the coating liquid. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram showing the major and minor axes of irregular-shaped particles. [Diagram 2] FIG. 2 is a schematic diagram showing buried and exposed portions of an irregularly shaped particle. [Diagram 3] FIG. 3 is a schematic diagram for explaining step [1] in the device manufacturing method. [Figure 4] FIG. 4 is a schematic diagram for explaining step [2] in the device manufacturing method. [Diagram 5]FIG. 5 is a schematic diagram for explaining step [3] in the device manufacturing method. [Figure 6] FIG. 6 is a scanning electron microscope photograph of the surface of the coating layer of Example 2. [Figure 7] FIG. 7 is a scanning electron microscope photograph of the surface of the coating layer of Example 8. [Figure 8] FIG. 8 is a scanning electron microscope photograph of the surface of the coating layer of Example 9. [Figure 9] FIG. 9 is a scanning electron microscope photograph of the surface of the coating layer of Comparative Example 1. [Figure 10] FIG. 10 is a scanning electron microscope photograph of the surface of the coating layer of Comparative Example 2. [Figure 11] FIG. 11 is a scanning electron microscope photograph of the surface of the coating layer of Comparative Example 3. [Figure 12] FIG. 12 is a scanning electron microscope photograph of the surface of the coating layer of Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiment for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiment. In this specification, "(meth)acryloyl group" refers to a methacryloyl group or an acryloyl group, and "(meth)acrylate" refers to a methacrylate or an acrylate. Unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more.

[0012] The coating liquid according to the present embodiment contains (1) irregularly shaped particles, (2) a polymer, (3) a poor solvent for the polymer, and (4) a good solvent for the polymer, the good solvent having a boiling point lower than that of the poor solvent. In the coating liquid, the ratio of the volume of component (1) to the volume of component (2) is 1 / 4 to 10 / 1, the ratio of the volume of component (1) to the sum of the volumes of components (2) and (3) is 1 / 10 to 1 / 2, and the ratio of the volume of component (4) to the volume of component (3) is 1 / 1 to 100 / 1.

[0013] According to the coating liquid of this embodiment, it is possible to form a coating layer having a polymer layer and irregularly shaped particles, the irregularly shaped particles having portions embedded in the polymer layer and portions exposed from the polymer layer, and protrusions formed on the surface by the portions of the irregularly shaped particles exposed from the polymer layer. Since the coating layer has protrusions showing high strength and high uniformity, it can be suitably used for applications such as biological sample collection devices. In this specification, a "biological sample" is a sample obtained from an animal (e.g., a human) or a plant. Examples of biological samples include urine, blood, tissue, cells, and extracellular vesicles. These biological samples may contain DNA, RNA (e.g., miRNA), proteins, etc.

[0014] <(1) Irregularly shaped particles> The irregularly shaped particles are particles having shape anisotropy. The term "having shape anisotropy" means that the shape is other than a sphere and other than a regular polyhedron.

[0015] In this specification, the "long axis of the irregular-shaped particle" refers to the maximum particle size of the irregular-shaped particle. The "short axis of the irregular-shaped particle" refers to the maximum particle size in the direction perpendicular to the axis (major axis) of the major axis of the irregular-shaped particle. The long axis and short axis of the irregular-shaped particle can be calculated by measuring these lengths on a scanning electron microscope photograph.

[0016] Fig. 1 is an example of an irregular-shaped particle. In the irregular-shaped particle 4 shown in Fig. 1, L indicates the major axis and S indicates the minor axis. Fig. 2 is an example of a protrusion formed by the irregular-shaped particle 4. By embedding the irregular-shaped particle 4 in the polymer layer 3 as shown in Fig. 2, embedded portions 4a and exposed portions 4b are formed. The irregular-shaped particle 4 is fixed to the polymer layer 3 at the embedded portions 4a, and protrusions are formed by the exposed portions 4b.

[0017] The major axis of the irregular-shaped particles is preferably 0.1 to 100 μm, since it is possible to expose the irregular-shaped particles from the polymer layer while partially embedding the irregular-shaped particles in the polymer layer, and to increase the surface area of ​​the protrusions and improve the performance of capturing biological samples. The major axis of the irregular-shaped particles is preferably 0.2 μm or more, 0.5 μm or more, 1.0 μm or more, 2.0 μm or more, 3.0 μm or more, 4.0 μm or more, 5.0 μm or more, 8.0 μm or more, or 10.0 μm or more, since it is suitable for improving the performance of capturing biological samples. The major axis of the irregular particles is preferably 80.0 μm or less, 50.0 μm or less, 30.0 μm or less, 20.0 μm or less, 15.0 μm or less, 12.0 μm or less, 10.0 μm or less, 8.0 μm or less, 6.0 μm or less, 5.0 μm or less, 3.0 μm or less, or 1.0 μm or less, since this is suitable for improving the strength of the protrusions.

[0018] The minor axis of the irregular-shaped particles is preferably 0.01 to 10 μm, since the strength of the irregular-shaped particles can be increased to improve the strength of the protrusions while increasing the surface area of ​​the protrusions to improve the performance of capturing biological samples. The minor axis of the irregular-shaped particles is preferably 0.02 μm or more, 0.04 μm or more, 0.05 μm or more, 0.10 μm or more, or 0.15 μm or more, since it is suitable for increasing the strength of the protrusions, and may be 1.0 μm or more or 5.0 μm or more. The minor axis of the irregular-shaped particles is preferably 8.0 μm or less, 4.0 μm or less, 2.0 μm or less, 1.0 μm or less, 0.50 μm or less, 0.40 μm or less, or 0.30 μm or less, since it is suitable for improving the performance of capturing biological samples.

[0019] The ratio (L / S) of the major axis (unit: μm) of the irregular-shaped particle to the minor axis (unit: μm) of the irregular-shaped particle is preferably 2.0 or more, since both the embedded portion of the irregular-shaped particle in the polymer layer and the exposed portion from the polymer layer can be made longer, and both the strength of the protrusions and the performance of capturing a biological sample can be achieved. The ratio of the major axis of the irregular-shaped particle to the minor axis of the irregular-shaped particle is more preferably 3.0 or more, 4.0 or more, 5.0 or more, 8.0 or more, 10.0 or more, 15.0 or more, 20.0 or more, 25.0 or more, 50.0 or more, 75.0 or more, or 100.0 or more, since this is suitable for improving the strength of the protrusions and the performance of capturing a biological sample. The ratio of the major axis of the irregular-shaped particle to the minor axis of the irregular-shaped particle may be 150 or less, 125 or less, 100 or less, 75 or less, 50 or less, 30 or less, or 25 or less.

[0020] The material of the irregular shaped particles is not particularly limited, but from the viewpoint of ease of particle synthesis, examples include silica, zinc oxide, titanium oxide, nickel oxide, alumina oxide, yttria oxide, tin oxide, indium oxide, indium tin oxide, silicon carbide, gold, silver, carbon, silicon nitride, etc. The material of the irregular shaped particles preferably includes at least one selected from the group consisting of zinc oxide and titanium oxide, because the irregular shaped particles are particularly easy to synthesize.

[0021] The irregularly shaped particles may be surface-modified with a silane coupling agent. The silane coupling agent may have a reactive functional group such as an ethylenically unsaturated group (e.g., a vinyl group, a (meth)acryloyl group), an epoxy group, an amino group, an isocyanurate group, an isocyanate group, a ureido group, a mercapto group, or a polysulfide group (e.g., a tetrasulfide group).

[0022] Examples of silane coupling agents having a (meth)acryloyl group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane. Examples of silane coupling agents having a vinyl group include vinyltrimethoxysilane, vinyltriethoxysilane, and p-styryltrimethoxysilane. Examples of silane coupling agents having an epoxy group include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-glycidoxypropyltrimethoxysilane. Examples of silane coupling agents having an amino group include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane. An example of a silane coupling agent having an isocyanurate group is tris-(trimethoxysilylpropyl)isocyanurate. An example of a silane coupling agent having an isocyanate group is 3-isocyanatepropyltriethoxysilane. An example of a silane coupling agent having an ureido group is 3-ureidopropyltrialkoxysilane. An example of a silane coupling agent having a mercapto group is 3-mercaptopropylmethyldimethoxysilane. An example of a silane coupling agent having a polysulfide group is bis(triethoxysilylpropyl)tetrasulfide.

[0023] The silane coupling agent is preferably a silane coupling agent having a (meth)acryloyl group.

[0024] The difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer is preferably 5 or less. The small difference in solubility parameter between the component constituting the surface of the irregular-shaped particle at the embedded portion in the polymer layer and the polymer increases the compatibility between the irregular-shaped particle and the polymer, making it difficult for the irregular-shaped particle to detach from the polymer layer, and thus the strength of the protrusions can be further increased. Since this is suitable for increasing the strength of the protrusions, the difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer is more preferably 4 or less, even more preferably 3 or less, and most preferably 2 or less. In this specification, the Hansen solubility parameter (HSP value) is used as the value of the solubility parameter.

[0025] The solubility parameter of the silane coupling agent may be 10 or more, 11 or more, or 12 or more, and may be 15 or less, 14 or less, or 13 or less.

[0026] The degree of dispersion (polydispersity index), which is an index of particle size distribution of irregular particles, is preferably 10% or less, more preferably 8% or less, and particularly preferably 5% or less, since this is suitable for suppressing the variation of protrusions in the coating layer and keeping the amount of collected biological sample constant. In this specification, the "degree of dispersion" is measured by dynamic light scattering, and the polydispersity index obtained by the cumulant method is used as the degree of dispersion.

[0027] The content of the irregular particles may be 1.0% by mass or more, 3.0% by mass or more, 5.0% by mass or more, 7.0% by mass or more, 9.0% by mass or more, 11.0% by mass or more, 13.0% by mass or more, 15.0% by mass or more, or 17.0% by mass or more based on the total mass of the coating liquid, and may be 25.0% by mass or less, 20.0% by mass or less, 18.0% by mass or less, 15.0% by mass or less, 13.0% by mass or less, 11.0% by mass or less, or 9.0% by mass or less. When the irregular particles are surface-modified with a silane coupling agent, the total content of the irregular particles and the silane coupling agent may be within the above-mentioned range as the content of the irregular particles.

[0028] <(2) Polymer> The coating liquid contains a polymer. Examples of the polymer include poly(meth)acrylates such as polymethyl(meth)acrylate and poly(ethyl)acrylate, polytrimethylolpropane ethoxy tri(meth)acrylate, polypentaerythritol ethoxy tetra(meth)acrylate, polytrimethylolpropane propoxy tri(meth)acrylate, polypentaerythritol tri(meth)acrylate, polypentaerythritol tetra(meth)acrylate, polydipentaerythritol hexa(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytricyclodecane dimethanol di(meth)acrylate, and polyethoxylated phenyl(meth)acrylate. aliphatic polymers such as polystyrene, poly-α-methylstyrene, polyvinyltoluene, poly-p-methylstyrene, poly-2-methylstyrene, poly-3-methylstyrene, poly-4-methylstyrene, poly-4-ethylstyrene, poly-4-tert-butylstyrene, poly-3,4-dimethylstyrene, poly-4-methoxystyrene, poly-4-ethoxystyrene, poly-2-chlorostyrene, poly-3-chlorostyrene, poly-4-chlorostyrene, poly-2,4-dichlorostyrene, poly-2,6-dichlorostyrene, poly-4-chloro-3-methylstyrene, polydivinylbenzene, poly-1-vinylnaphthalene, poly-2-vinylpyridine, poly-4-vinylpyridine, poly-sodium p-styrenesulfonate, and other aromatic polymers.

[0029] The polymer preferably includes one selected from the group consisting of polymethyl (meth)acrylate and polystyrene, because of its availability. The polymer may be a homopolymer obtained by polymerization of a single corresponding monomer, or a copolymer obtained by polymerization of a mixture of a plurality of monomers. When obtaining a polymer by polymerization of a monomer, various additives may be used as necessary. Examples of additives include initiators, antioxidants, polymerization inhibitors, leveling agents, silane coupling agents, and the like. When obtaining a polymer by polymerization of a monomer, it is preferable to use an initiator. Examples of initiators include potassium peroxodisulfate, hydrogen peroxide, azobisisobutyronitrile, benzoyl peroxide, and the like.

[0030] The solubility parameter of the polymer may be 7 or more, 8 or more, or 9 or more, and may be 12 or less, 11 or less, or 10 or less.

[0031] The polymer content, based on the total mass of the coating liquid, may be 1.0 mass% or more, 2.0 mass% or more, 3.0 mass% or more, 4.0 mass% or more, 5.0 mass% or more, or 6.0 mass% or more, and may be 20.0 mass% or less, 15.0 mass% or less, 12.0 mass% or less, 10.0 mass% or less, 8.5 mass% or less, or 7.0 mass% or less.

[0032] <Poor solvent for polymer> The coating liquid contains a poor solvent for the polymer. A "poor solvent for the polymer" refers to a liquid that does not dissolve the polymer or does not easily dissolve the polymer. When a powdered polymer is placed in a liquid and stirred for 24 hours, and then the solid is recovered from the liquid and dried, if the weight loss from the original polymer is less than 50%, the liquid is a poor solvent for the polymer.

[0033] When the coating liquid contains a poor solvent for the polymer, the polymer becomes insoluble when the good solvent for the polymer evaporates, and the irregularly shaped particles are fixed. When the good solvent for the polymer evaporates, the presence of the poor solvent prevents the irregularly shaped particles from being exposed above the liquid surface, and the particles are fixed in this state, making it possible to suppress particle aggregation. As a result, protrusions are formed on the surface of the coating layer with high uniformity. If the coating liquid does not contain a poor solvent, the irregularly shaped particles are not fixed when the good solvent evaporates, and the particles aggregate, resulting in areas where protrusions are not formed or variations in the structure of the protrusions.

[0034] The poor solvent for the polymer preferably has a fluorine group (-F). In this case, when the surface tension of the poor solvent for the polymer decreases and the good solvent for the polymer volatilizes, a two-layer structure is more likely to be formed, with the poor solvent for the polymer in the upper layer of the coating liquid and the insoluble polymer in the lower layer. This makes it easier to form a structure in which the polymer fixes the bases of the irregularly shaped particles, making it possible to form protrusions with even greater strength.

[0035] Examples of poor solvents for polymers having fluorine groups include, but are not limited to, monofluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, hexafluorobenzene, octafluorocyclopentene, hexafluoroisopropyl methyl ether, octafluorotoluene, tetradecafluoromethylcyclohexane, eicosafluorononane, octafluorooctane, 1,3-bis(trifluoromethyl)benzene, tetradecafluoro-2-methylpentane, hexadecafluoro-n-octylbromo amide, tetradecafluorohexane, pentadecafluorotriethylamine, hexacosafluorododecane, hexadecafluoroheptane, hexadecafluoro(1,3-dimethylcyclohexane), heptacosafluorotributylamine, octadecafluorodecahydronaphthalene perfluorodecalin, perfluoro(2-butyltetrahydrofuran), perfluorotriamylamine, 1,1,2-trichlorotrifluoroethane, 1,2-dichlorotetrafluoroethane, 1,3-dichlorotetrafluoropropane, 1-chloro-1,2,2 ,2-tetrafluoroethane, 1-bromo-1,1,2,2-tetrafluoroethane, 1-fluoro-1,2-dichloroethane, 1-fluoro-2,2,3,3-tetrachloropropene, 1-fluoro-2,2,3,3-tetrafluoropropene, 1-fluoro-2,3,3,3-tetrachloropropene, 1-fluoro-3,3-dichloropropene, 1-fluoro-4-chloro-2-nitrobenzene, 1,1,1-trifluoroethane, 1,1,2-trichloro-1,2,2-trifluoroethane, 1,1-dichloro-1-fluoroethane, 1,1- Dichloro-2,2,2-trifluoroethane, 1,2,2-trifluoroethane, 1,2-dichloro-1,1,2,2-tetrafluoroethane, 1,2-dichloro-1,2,2-trifluoroethane, 1,2-dichloro-1,2,2-trifluoroethanol, 1,2-difluoro-1,2-dichloroethylene, 1,2-difluoroethane, 1,3-dichloro-1,1,2,2-tetrafluoroethane, 1,3-dichloro-1,2,2-trifluoropropane, 1,4-difluorobenzene, 2,2-dichloro-1,1,1-trifluoroethane, 2,Examples of the fluorocarbon include 2-difluoroethane, 2,3-difluoro-1,1,2,2-tetrachloroethane, 2,3-difluoro-1,1,2,2-tetrafluoroethane, 2,4-difluorobenzene, 3,3-dichloro-1,1,1-trifluoropropene, 3,3-dichloro-1,1,2,2-tetrafluoropropene, 3,3-difluoro-1,2-dichloropropene, 3,3-difluoro-1,2-epoxypropane, and 3,4-difluoro-1,1,2,2-tetrachloroethane.

[0036] The surface tension of the poor solvent for the polymer is preferably 22 mN / m or less. By having a surface tension of 22 mN / m or less, the poor solvent is likely to gather on the surface of the coating layer, and a two-layer structure of the poor solvent and the polymer is likely to be formed. The surface tension of the poor solvent for the polymer is more preferably 20 mN / m or less, even more preferably 18 mN / m or less, and most preferably 16 mN / m or less. From the viewpoint of suppressing the effect of natural destruction when discharged into the environment, a higher surface tension is preferable, and therefore the surface tension is preferably 13 N / m or more, more preferably 15 N / m or more, even more preferably 17 N / m or more, and most preferably 19 N / m or more.

[0037] The boiling point of the poor solvent for the polymer is preferably 200° C. or less, 175° C. or less, or 150° C. or less under atmospheric pressure in order to reduce the drying time of the coating, and may be 140° C. or less, 130° C. or less, 120° C. or less, or 100° C. or less. The boiling point of the poor solvent for the polymer is higher than the boiling point of the good solvent for the polymer under atmospheric pressure, and may be 80° C. or more, 90° C. or more, 100° C. or more, or 110° C. or more.

[0038] The content of the poor solvent for the polymer may be 1.0 mass% or more, 2.0 mass% or more, 3.0 mass% or more, 4.0 mass% or more, 5.0 mass% or more, or 6.0 mass% or more, and may be 20.0 mass% or less, 15.0 mass% or less, 12.0 mass% or less, 10.0 mass% or less, 8.5 mass% or less, or 7.0 mass% or less, based on the total mass of the coating liquid.

[0039] <Good solvent for polymers> The coating liquid contains a good solvent for the polymer. A "good solvent for a polymer" refers to a liquid that dissolves the polymer. When a powdered polymer is placed in a liquid and stirred for 24 hours, and then the solid is recovered from the liquid and dried, if the weight loss from the original polymer is 50% or more, the liquid is a good solvent for the polymer.

[0040] By including a good solvent for the polymer, the polymer remains dissolved in the coating liquid before application, which improves the uniformity of the coating (coating film). If the coating liquid does not include a good solvent for the polymer, the insolubilized polymer solid and irregularly shaped particles remain dispersed in the coating liquid, and the coated irregularly shaped particles cannot be fixed to the support substrate, resulting in a decrease in the strength of the protrusions. The good solvent evaporates first, forming the aforementioned two-layer structure of poor solvent and polymer, and the boiling point of the good solvent is lower than that of the poor solvent.

[0041] The difference (T3-T4) between the boiling point T3 of the poor solvent for the polymer under atmospheric pressure and the boiling point T4 of the good solvent for the polymer under atmospheric pressure is preferably 10° C. or more, more preferably 20° C. or more, and most preferably 30° C. or more, since this facilitates the formation of a two-layer structure of the poor solvent and the polymer and is more suitable for increasing the strength of the protrusions. If the boiling point is too low, it may cause the coating liquid to dry out during storage, so T3-T4 is preferably 70° C. or less or 50° C. or less, and may be 40° C. or less, 30° C. or less, or 10° C. or less.

[0042] The boiling point of a good solvent for the polymer under atmospheric pressure may be 90°C or lower, 80°C or lower, 70°C or lower, 60°C or lower, 50°C or lower, or 40°C or lower, or may be 30°C or higher, 40°C or higher, 50°C or higher, or 60°C or higher.

[0043] Suitable solvents for the polymer include methyl ethyl ketone, dimethylformamide, acetone, tetrahydrofuran, toluene, and ethyl acetate.

[0044] The content of the good solvent for the polymer may be 50 mass % or more, 60 mass % or more, or 70 mass % or more, and may be 90 mass % or less, 85 mass % or less, or 80 mass % or less, based on the total amount of the coating liquid.

[0045] <Ingredient (1) / Ingredient (2)> The ratio of the volume of component (1) (irregularly shaped particles) to the volume of component (2) (polymer) (component (1) / component (2)) is 1 / 4 to 10 / 1. When component (1) / component (2) is within this range, the irregularly shaped particles are fixed with the polymer to increase the strength of the protrusions, while the irregularly shaped particles are not completely buried in the polymer, making it possible to form protrusions. Since this is suitable for increasing the strength of the protrusions, the upper limit of component (1) / component (2) is preferably 8 / 1 or less, more preferably 6 / 1 or less, even more preferably 4 / 1 or less, and most preferably 2 / 1 or less. Since this is suitable for increasing the height of the protrusions and improving the capturing performance of biological samples, the lower limit of component (1) / component (2) is preferably 1 / 3 or more, more preferably 1 / 2 or more, even more preferably 1 / 1 or more, and most preferably 2 / 1 or more.

[0046] <Component (1) / [Component (2)+Component (3)]> The ratio of the volume of component (1) (irregular particles) to the total volume of component (2) (polymer) and component (3) (poor solvent for polymer) (component (1) / [component (2)+component (3)]) is 1 / 10 to 1 / 2. When component (1) / [component (2)+component (3)] is in the above range, a two-layer structure of poor solvent and polymer is formed when the good solvent evaporates, and aggregation of irregular particles can be suppressed. Since it is suitable for suppressing aggregation of irregular particles, the upper limit of component (1) / [component (2)+component (3)] is preferably 1 / 3 or less, more preferably 1 / 4 or less, and most preferably 1 / 5 or less. Since it is suitable for suppressing irregular particles that are not fixed to the polymer from being included in the coating layer, the lower limit of component (1) / [component (2)+component (3)] is preferably 1 / 8 or more, more preferably 1 / 6 or more, even more preferably 1 / 4 or more, and most preferably 1 / 3 or more.

[0047] <Ingredient (4) / Ingredient (3)> The volume ratio of component (4) (good solvent for polymer) to the volume of component (3) (poor solvent for polymer) (component (4) / component (3)) is 1 / 1 to 100 / 1. When component (4) / component (3) is in the above range, the polymer contained in the coating liquid can be dissolved, and a uniform coating layer can be formed. In addition, when the good solvent evaporates, a two-layer structure of the poor solvent and the polymer is formed. Since it is suitable for dissolving the polymer contained in the coating liquid, component (4) / component (3) is preferably 2 / 1 or more, more preferably 5 / 1 or more, even more preferably 10 / 1 or more, and most preferably 20 / 1 or more. In addition, since it is suitable for forming a two-layer structure of the poor solvent and the polymer when the good solvent evaporates, component (4) / component (3) is preferably 50 / 1 or less, more preferably 30 / 1 or less, even more preferably 15 / 1 or less, and most preferably 8 / 1 or less.

[0048] <Protrusion formation method> The method for forming protrusions using the coating liquid of the present invention includes the following steps [1] to [3]. [1] A step of applying the coating liquid to a supporting substrate to form a coating film containing the coating liquid. [2] A process to volatilize the good solvent for the polymer from the coating film and make the polymer insoluble [3] A step of volatilizing the poor solvent for the polymer from the coating film in which the polymer has been insolubilized.

[0049] <Process [1]> As shown in Fig. 3, in step [1], a coating liquid is applied to a supporting substrate 1 to form a coating film 9. The coating film 9 is formed on the supporting substrate 1 and contains irregularly shaped particles 4 and a mixture 6 of a polymer, a poor solvent for the polymer, and a good solvent for the polymer.

[0050] The material of the supporting substrate 1 is not particularly limited, and examples thereof include resin, glass, ceramics, etc. The supporting substrate 1 may be a substrate of any shape, such as a film, a sheet, a plate, or a structure having a curved surface.

[0051] Resins that can be used as the supporting substrate 1 include cellulose-based resins such as triacetyl cellulose, diacetyl cellulose, and acetate butyrate cellulose; polyester resins such as polyethylene terephthalate; polycarbonate resins; acrylic resins such as polymethyl methacrylate; polyurethane resins; polyether resins; polysulfone resins; polyethersulfone; polyether ketone, and the like.

[0052] A coating layer such as a hard coat layer, an anchor coat layer, or a polymer electrolyte layer may be formed on the surface of the supporting substrate 1 in order to improve scratch resistance and adhesion, and surface treatment such as UV ozone cleaning, plasma treatment, or corona treatment may be performed in order to improve adhesion and coatability.

[0053] The method for applying the coating liquid to the supporting substrate 1 is not particularly limited, but various commonly known methods can be used, such as brush coating, dip coating, spin coating, bar coating, flow coating, spray coating, roll coating, air knife coating, blade coating, gravure coating, microgravure coating, and slot die coating.

[0054] <Process [2]> In step [2], the good solvent for the polymer is volatilized from the coating film 9 to insolubilize the polymer. As shown in Figure 4, by insolubilizing the polymer, a two-layer structure consisting of a poor solvent 7 for the polymer and a polymer layer 3 containing the insolubilized polymer is formed. The polymer layer 3 fixes the irregularly shaped particles 4 onto the support substrate 1.

[0055] The method for volatilizing the good solvent for the polymer is not particularly limited, and various commonly known methods such as heat drying, vacuum drying, air drying, UV drying, etc. can be used.

[0056] <Process [3]> In step [3], the poor solvent for the polymer is volatilized from the coating film in which the polymer has been insolubilized. As shown in Fig. 5, by removing the poor solvent 7 for the polymer, a coating layer 2 including a polymer layer 3 and irregularly shaped particles 4 fixed to the polymer layer 3 is formed on the support substrate 1. As shown in Fig. 2, protrusions 5 are formed by exposed portions 4b of the irregularly shaped particles 4 from the polymer layer 3.

[0057] The method for volatilizing the poor solvent 7 of the polymer is not particularly limited, and the drying method described above for volatilizing the good solvent of the polymer can be applied.

[0058] <Other processes> The method for forming protrusions may further include a step of covering at least a part of the surface of coating layer 2 opposite to the side on which protrusions 5 are present, with a covering layer.

[0059] The coating layer may be, for example, an inorganic oxide layer or an ionic polymer layer. When the coating layer is an inorganic oxide layer or an ionic polymer layer, it is possible to further increase the capture rate of extracellular vesicles.

[0060] The inorganic oxide layer contains an inorganic oxide, such as zinc oxide (ZnO), alumina oxide (Al2O3), silica (SiO2), nickel oxide (NiO), titanium oxide (TiO2), yttria oxide (Y2O3), tin oxide (e.g., SnO), indium oxide, and indium tin oxide (ITO).

[0061] Since the inorganic oxide layer is suitable for increasing the capture rate of extracellular vesicles, it preferably contains at least one selected from the group consisting of zinc oxide, alumina oxide, silica, nickel oxide, titanium oxide, yttria oxide, tin oxide, and indium tin oxide, and more preferably contains at least one selected from the group consisting of zinc oxide, titanium oxide, and indium tin oxide.

[0062] The method for forming an inorganic oxide layer on the surface of the coating layer 2 is not particularly limited, but examples include a method in which the desired inorganic oxide is directly coated by sputtering, chemical vapor deposition, deposition, etc., and a method in which a precursor of the inorganic oxide is wet-coated and then grown into the inorganic oxide by a sol-gel method.

[0063] The ionic polymer layer may contain a cationic polymer and / or an anionic polymer. The cationic polymer is preferably a polymer containing a secondary amino group, a tertiary amino group, or a quaternary ammonium group. Examples of the cationic polymer include polyelectrolytes such as polyethyleneimine and its quaternary derivatives, polydiallyldimethylammonium chloride, poly(N,N'-dimethyl-3,5-dimethylene-piperidinium chloride) polyallylamine and its quaternary derivatives, polydimethylaminoethyl(meth)acrylate and its quaternary derivatives, and polydimethylaminopropyl(meth)acrylamide and its quaternary derivatives.

[0064] Anionic polymers are -COOH, -COO - , -SO3H, or -SO3 - Examples of the anionic polymer include poly(meth)acrylic acid and its ionized products, poly(sodium polystyrenesulfonate), poly(2-acrylamido-2-methyl-1-propanesulfonic acid), polyamic acid, and poly(potassium vinylsulfonate).

[0065] The ionic polymer layer preferably contains a cationic polymer, since it is possible to further increase the extracellular vesicle capture rate. The ionic polymer layer preferably contains a cationic polymer and does not contain an anionic polymer (cationic polymer layer), or contains a cationic polymer and an anionic polymer, since it is possible to further increase the extracellular vesicle capture rate.

[0066] The method of forming an ionic polymer layer on the surface of the coating layer 2 is not particularly limited, and can be appropriately selected depending on the material of the irregularly shaped particles 4 and the types of cationic polymer and anionic polymer. For example, a method including surface-treating the surface of the coating layer 2 on which the protrusions 5 are provided, and attaching a liquid containing a cationic polymer or anionic polymer to the surface-treated surface of the coating layer 2, washing with water or the like as necessary, and then drying can be used. For example, plasma treatment can be used for the surface treatment. For example, a method of forming an ionic polymer layer containing a cationic polymer and an anionic polymer on the surface of the coating layer 2 can be used, in which the surface of the coating layer 2 is coated with one of the cationic polymer and the anionic polymer, and then coated with the other polymer.

[0067] <Device creation process> The method for forming protrusions may further include a step of forming the formed protrusions into a device for use in collecting biological samples or the like (device forming step).

[0068] The device formation step may be, for example, a step of attaching a coated substrate having one or more through-holes to the surface of the coating layer 2 on which the protrusions are present, and forming a space for adding a biological sample by at least one of the through-holes. There is no particular limitation on the method for attaching the coated substrate to the coating layer 2, and physical or chemical attachment methods such as adhesive tape, adhesives, and fusion by heating can be used.

[0069] The device formation step may include, for example, a step of adhering a coated substrate having one or more through holes to the surface of the coating layer 2 on which the protrusions are present, via an intermediate layer having an area for adhering these and an internal space forming a flow path for transporting a biological sample. The intermediate layer can be formed, for example, from an adhesive tape. In this case, the coating layer 2 and the coated substrate are attached to each other with the adhesive tape, and the area (internal space) where the adhesive tape is not present can be used as the flow path.

[0070] <Protrusion> The ratio of the height (unit: μm) of the protrusions 5 to the major axis (unit: μm) of the irregular-shaped particles 4 (height of the protrusions 5 / major axis of the irregular-shaped particles 4) is preferably 0.10 to 0.95. By having the ratio of the height of the protrusions 5 to the major axis of the irregular-shaped particles 4 in the above range, it is possible to achieve both the strength of the protrusions 5 and the performance of capturing a biological sample. Since it is suitable for improving the performance of capturing a biological sample, it is preferable that the ratio of the height of the protrusions 5 to the major axis of the irregular-shaped particles 4 is 0.20 or more, 0.30 or more, 0.50 or more, 0.60 or more, 0.70 or more, or 0.80 or more. Since it is suitable for increasing the strength of the protrusions 5, it is preferable that the ratio of the height of the protrusions 5 to the major axis of the irregular-shaped particles 4 is 0.90 or less, 0.85 or less, 0.80 or less, 0.75 or less, or 0.70 or less, and may be 0.60 or less, or 0.40 or less.

[0071] When the coating layer 2 is viewed from the side where the protrusions 5 are present, the ratio of the area of ​​the region where the protrusions 5 are present to the entire coating layer 2 (hereinafter also referred to as the "protrusion presence ratio") is preferably 10% or more. When the protrusion presence ratio is 10% or more, the performance of capturing a biological sample can be improved. Since this is suitable for improving the performance of capturing a biological sample, the protrusion presence ratio is preferably 30.0% or more, 50.0% or more, 60.0% or more, 70.0% or more, or 80.0% or more. The protrusion presence ratio may be, for example, 100.0% or less, 95.0% or less, 90.0% or less, or 85.0% or less.

[0072] The protrusion presence ratio can be determined by observing the surface of the coating layer 2 on which the protrusions 5 are present with a scanning electron microscope from a direction perpendicular to the surface, and dividing the area in the obtained scanning electron microscope image in which the protrusions 5 (irregularly shaped particles 4 exposed from the polymer layer 3) are present by the area of ​​the measurement range. Here, the measurement range is a range equivalent to the area of ​​a square with one side 100 times or more the minor axis of the irregularly shaped particles 4 that form the protrusions 5. Details of the measurement method may be as described in the examples.

[0073] The standard deviation of the protrusion presence ratio is preferably 10.00 or less. The standard deviation of the protrusion presence ratio can be used as an index of variation. The lower the standard deviation of the protrusion presence ratio, the more uniform the protrusions are present. The standard deviation of the protrusion presence ratio is preferably 8.00 or less, 7.00 or less, 6.00 or less, 5.00 or less, 4.00 or less, 3.00 or less, 2.50 or less, 2.00 or less, 1.50 or less, or 1.00 or less. The standard deviation of the protrusion presence ratio may be, for example, 0.30 or more, 0.60 or more, or 0.90 or more. The standard deviation of the protrusion presence ratio can be determined by a method including randomly selecting five square areas with sides of 10 μm in an image obtained by measuring the surface of the coating layer 2 on the side where the protrusions 5 are present with a scanning electron microscope from a direction perpendicular to the surface, determining the protrusion presence ratio, and calculating the standard deviation of the measurement results of the protrusion presence ratio of the five points.

[0074] In the coating layer 2, the number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 is preferably 50% or less of the total number of irregular-shaped particles 4. By making the number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 50% or less of the total number of irregular-shaped particles 4, contamination of the irregular-shaped particles 4 due to inclusion when the biological sample is contacted can be suppressed. Since it is suitable for suppressing contamination of the biological sample due to inclusion of irregular-shaped particles, the number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 is more preferably 30% or less of the total number of irregular-shaped particles 4, further preferably 10% or less, and most preferably 5% or less. The number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 can be obtained by immersing the biological sample collection device in pure water and irradiating it with ultrasound to peel off and recover the particles from the device, and the number of particles can be measured. In addition, the total number of irregular-shaped particles 4 contained in the coating layer 2 can be determined by recovering the irregular-shaped particles 4 after removing the polymer layer 3 by washing with a solvent or by baking, and counting the number of particles.

[0075] The length of the support substrate 1 in the out-of-plane direction from the surface of the support substrate 1 on the coating layer 2 side to the apex of the protrusion 5 is preferably 10 times or less than the major axis of the irregular particles 4. By making the length of the support substrate 1 in the out-of-plane direction from the surface of the support substrate 1 on the coating layer 2 side to the apex of the protrusion 5 10 times or less than the major axis of the irregular particles 4, the film thickness of the coating layer 2 can be made thin, resulting in a device with excellent flexibility. Since this is suitable for increasing flexibility, the length of the support substrate 1 in the out-of-plane direction from the surface of the support substrate 1 on the coating layer 2 side to the apex of the protrusion 5 is more preferably 5 times or less than the major axis of the irregular particles 4, even more preferably 2 times or less than the major axis of the irregular particles 4, and most preferably less than the major axis of the irregular particles 4.

[0076] In the application of collecting cells, it is preferable that the protrusions 5 formed by the exposed irregularly shaped particles 4 are oriented in one direction. In the case of a biological sample collection device having a flow channel structure, the protrusions 5 are arranged against the flow of the biological sample in the flow channel, and the collection efficiency of the biological sample by the protrusions 5 can be increased. In addition, in the case of biological samples such as cells, the components inside the biological sample are easily extracted by crushing with the protrusions 5. The orientation of the protrusions 5 in one direction can be determined by the presence or absence of bright spots in the Fourier transform image obtained by measuring a scanning electron microscope image of the surface of the biological sample collection device and Fourier transforming the image. By the Fourier transform, it is possible to convert the shading of the original image into a two-dimensional image representing the power (square of the absolute value of the brightness) for the wave number of each sine wave when the shading of the original image is approximated by superposition of sine waves, and if there is regularity in the shading of the original image, bright spots corresponding to each sine wave will appear in the Fourier transform image.

[0077] In applications involving the collection of extracellular vesicles, it is preferable that the protrusions 5 formed by the exposed irregularly shaped particles 4 are irregularly arranged. By having the protrusions 5 formed by the exposed irregularly shaped particles 4 be irregularly arranged rather than oriented in one direction, in the case of a biological sample collection device having a flow channel structure, the reproducibility of the biological sample collection efficiency can be stabilized, independent of the direction of the protrusions 5 in the flow channel. EXAMPLES

[0078] The present invention will be described in more detail below based on examples. However, the present invention is not limited to these. In the examples and comparative examples, the major axis and minor axis of the irregular-shaped particles and the strength were confirmed, and the area ratio where the protrusions were formed was calculated by the following methods.

[0079] [Measurement of major and minor diameters of irregularly shaped particles] (Preparation of measurement samples) A measurement sample was prepared by casting and drying the irregular particle dispersion on a collodion-supported copper mesh. The irregular particle dispersion was prepared by adding 10 mg of irregular particles to 1 mL of methanol and dispersing them by ultrasonic irradiation for 10 seconds.

[0080] (measurement) A scanning electron microscope (Keyence VE-9800) was used to obtain a scanning electron microscope photograph of the measurement sample. The long diameter was calculated by measuring the maximum particle size of the irregularly shaped particles on the obtained photograph. The axis in the long diameter direction was taken as the long axis, and the short diameter was calculated by measuring the maximum length in the direction perpendicular to the long axis. The average of the long diameter and short diameter of 50 randomly selected particles was calculated. The calculated long diameter was divided by the short diameter to obtain the ratio of the long diameter to the short diameter (long diameter / short diameter).

[0081] [Strength check] The strength of the coating layer was evaluated by scratching the coating surface five times with a Bencot (manufactured by Asahi Kasei Corporation) under a load of 50 g, and checking for peeling of the coating layer from the supporting substrate both visually and using a scanning electron microscope. ◯: No peeling of the coating layer. ×: Peeling of the coating layer occurred.

[0082] [Proportion of area with protrusions] The surface of the coating layer was measured using a scanning electron microscope (Keyence VE-9800). On the obtained micrograph of the surface of the coating layer, the area where irregular particles were present was binarized as white, and the area where no irregular particles were present was black, and the ratio of the white area to the total area of ​​white and black was calculated. This was taken as the ratio of the area of ​​the area where the protrusions were present to the entire coating layer when the coating layer was viewed from the side where the protrusions were present.

[0083] [Uniformity of protrusions] On a photograph of the surface of the coating layer measured using a scanning electron microscope (Keyence VE-9800), five square areas with sides of 10 μm were randomly selected and the area ratio of the protrusions was calculated. The standard deviation of the measurement results of the five points was calculated and used as an index of variation.

[0084] [Example 1] 0.5 g of zinc oxide irregular particles (Sigma-Aldrich; major axis 4.5 μm, minor axis 0.2 μm, major axis / minor axis ratio 22.5) was added to 10 mL of methanol and dispersed by ultrasonic irradiation. 0.05 g of methacryloxypropyltrimethoxysilane (Tokyo Chemical Industry) (solubility parameter 12.5) and 0.05 g of 25% ammonia water (Fujifilm Wako Pure Chemical) were added to the obtained dispersion and reacted by stirring at 300 rpm using a stirrer at 60 ° C for 2 hours. After the reaction, the mixture was filtered through a 106 μm mesh filter to remove coarse aggregates, and the supernatant was collected by decantation. Methanol was added to the particles obtained after the reaction and centrifuged at 4000 rpm for 10 seconds, the supernatant was discarded, and the mixture was washed again with methanol. The obtained particles were then dried at room temperature to obtain irregular particles whose surfaces were modified with methacryloyl groups (solubility parameter 9.5).

[0085] 0.02 g of the irregular particles surface-modified with methacryloyl groups, 0.01 g of polymethyl methacrylate, 0.01 g of 1,3-bis(trifluoromethyl)benzene, and 0.12 g of methyl ethyl ketone were mixed. The mixture was irradiated with ultrasonic waves to disperse the particles. The obtained dispersion was spin-coated at 1000 rpm for 30 seconds on a polycarbonate film (manufactured by Teijin; product name Panlite), and then heated and dried at 60°C to form a coating layer consisting of irregular particles and a polymer layer.

[0086] The produced coating layer had excellent protrusion strength. The particles were densely distributed over the entire surface. In addition, protrusions accounted for 78.1% of the surface area, and many protrusions were formed on the surface. The physical properties of the obtained coating layer are shown in Table 1.

[0087] [Example 2] The coating liquid used was a mixture of 0.02 g of irregularly shaped particles surface-modified with methacryloyl groups, 0.005 g of polymethyl methacrylate, 0.015 g of 1,3-bis(trifluoromethyl)benzene, and 0.1 g of methyl ethyl ketone. The device was fabricated in the same manner as in Example 1.

[0088] The produced coating layer had excellent protrusion strength. The particles were densely present throughout. The area where protrusions were present was 69.1%, and many protrusions were formed on the surface. Figure 6 shows a scanning electron microscope photograph of the coating layer surface of Example 2.

[0089] [Example 3] The coating liquid used was a mixture of 0.02 g of irregularly shaped particles surface-modified with methacryloyl groups, 0.0025 g of polymethyl methacrylate, 0.0175 g of 1,3-bis(trifluoromethyl)benzene, and 0.09 g of methyl ethyl ketone. The rest of the procedure was the same as in Example 1, and the device was fabricated.

[0090] The produced coating layer had excellent protrusion strength. The particles were densely distributed over the entire surface. In addition, the area with protrusions was 57.2%, and many protrusions were formed on the surface.

[0091] [Example 4] The coating liquid used was a mixture of 0.02 g of irregularly shaped particles surface-modified with methacryloyl groups, 0.00125 g of polymethyl methacrylate, 0.01875 g of 1,3-bis(trifluoromethyl)benzene, and 0.085 g of methyl ethyl ketone. The rest of the procedure was the same as in Example 1, and the device was fabricated.

[0092] The produced coating layer had excellent protrusion strength. The particles were densely distributed over the entire surface. In addition, protrusions accounted for 78.5% of the surface area, and many protrusions were formed on the surface.

[0093] [Example 5] The coating liquid used was a mixture of 0.02 g of irregularly shaped particles surface-modified with methacryloyl groups, 0.00125 g of polymethyl methacrylate, 0.04375 g of 1,3-bis(trifluoromethyl)benzene, and 0.085 g of methyl ethyl ketone. The rest of the procedure was the same as in Example 1, and the device was fabricated.

[0094] The produced coating layer had excellent protrusion strength. The particles were densely distributed throughout the layer. In addition, protrusions accounted for 55.5% of the surface area, and many protrusions were formed on the surface.

[0095] [Example 6] A coating layer was formed in the same manner as in Example 2, except that irregularly shaped particles of zinc oxide (manufactured by Sigma-Aldrich; major axis 0.3 μm, minor axis 0.05 μm, major axis / minor axis ratio 6) were used.

[0096] The produced coating layer had excellent protrusion strength. The particles were densely distributed over the entire surface. In addition, protrusions accounted for 61.7% of the surface area, and many protrusions were formed on the surface.

[0097] [Example 7] A coating layer was formed in the same manner as in Example 2, except that irregularly shaped particles of zinc oxide (manufactured by Sigma-Aldrich; major axis 1 μm, minor axis 0.18 μm, major axis / minor axis ratio 5.6) were used.

[0098] The produced coating layer had excellent protrusion strength. The particles were densely distributed over the entire surface. In addition, protrusions accounted for 77.4% of the surface area, and many protrusions were formed on the surface.

[0099] [Example 8] A coating layer was formed in the same manner as in Example 2, except that irregularly shaped particles of titanium oxide (manufactured by Sigma-Aldrich; major axis 10 μm, minor axis 0.1 μm, major axis / minor axis ratio 100) were used.

[0100] The produced coating layer had excellent protrusion strength. The particles were densely present throughout. The area where protrusions were present was 81.2%, and many protrusions were formed on the surface. Figure 7 shows a scanning electron microscope photograph of the coating layer surface of Example 8.

[0101] [Example 9] A coating layer was formed in the same manner as in Example 2, except that polystyrene was used as the polymer.

[0102] The produced coating layer had excellent protrusion strength. Although there were areas where no particles were present, they were distributed uniformly. Furthermore, protrusions accounted for 51.7% of the surface area, and many protrusions were formed on the surface. Figure 8 shows a scanning electron microscope photograph of the coating layer surface of Example 9.

[0103] [Example 10] A coating layer was formed in the same manner as in Example 2, except that octadecafluorodecahydronaphthalene perfluorodecalin was used as a poor solvent.

[0104] The produced coating layer had excellent protrusion strength. The particles were densely distributed over the entire surface. In addition, protrusions accounted for 74.2% of the surface area, and many protrusions were formed on the surface.

[0105] [Comparative Example 1] A coating layer was formed in the same manner as in Example 1, except that no polymethyl methacrylate was added to the coating liquid.

[0106] The coating layer thus produced was inferior in strength. Fig. 9 shows a scanning electron microscope photograph of the surface of the coating layer of Comparative Example 1.

[0107] [Comparative Example 2] The coating liquid used was a mixture of 0.02 g of irregularly shaped particles surface-modified with methacryloyl groups, 0.04 g of polymethyl methacrylate, 0.01 g of 1,3-bis(trifluoromethyl)benzene, and 0.16 g of methyl ethyl ketone. The rest of the procedure was the same as in Example 1 to form a coating layer.

[0108] The coating layer thus produced had no protrusions on its surface. FIG. 10 shows a scanning electron microscope photograph of the coating layer surface of Comparative Example 2.

[0109] [Comparative Example 3] A coating layer was formed in the same manner as in Example 4, except that 1,3-bis(trifluoromethyl)benzene was not added.

[0110] The produced coating layer had a large variation in particle distribution. The produced coating layer had a small area where protrusions were present. Figure 11 shows a scanning electron microscope photograph of the coating layer surface of Comparative Example 3.

[0111] [Comparative Example 4] The coating liquid used was a mixture of 0.02 g of irregularly shaped particles surface-modified with methacrylic groups, 0.025 g of polymethyl methacrylate, 0.0975 g of 1,3-bis(trifluoromethyl)benzene, and 0.09 g of methyl ethyl ketone. The rest of the procedure was the same as in Example 3 to form a coating layer.

[0112] The coating layer thus produced had a small area where protrusions were present. FIG. 12 shows a scanning electron microscope photograph of the surface of the coating layer of Comparative Example 4.

[0113] The abbreviations in Table 1 are as follows. ZnO: zinc oxide, TiO2: titanium oxide, PMMA: polymethyl methacrylate, PS: polystyrene, TFMB: 1,3-bis(trifluoromethyl)benzene, ODFNPFD: octadecafluorodecahydronaphthalene perfluorodecalin.

[0114] In Examples 1 to 10 and Comparative Examples 1 to 4, the difference between the solubility parameter of the silane coupling agent having a methacryloyl group and the solubility parameter of the polymer was 3.2.

[0115] [Table 1]

[0116] As shown in Table 1, it was confirmed that by forming protrusions using a coating liquid containing components (1) to (4) and adjusted to specific ratios of component (2) / component (1), component (1) / [component (2)+component (3)], and component (4) / component (3), protrusions having excellent strength, a low standard deviation in the protrusion presence ratio, and a high protrusion presence ratio can be formed. [Explanation of symbols]

[0117] 1...support substrate, 2...coating layer, 3...polymer layer, 4...irregularly shaped particle, 4a...portion embedded in polymer layer, 4b...portion exposed from polymer layer, 5...projection, mixture of poor solvent and good solvent, 7...poor solvent, 10...device, S...minor axis of irregularly shaped particle, L...major axis of irregularly shaped particle

Claims

1. (1) irregularly shaped particles; (2) a polymer; (3) a poor solvent for the polymer; and (4) a good solvent for the polymer, the good solvent having a boiling point lower than that of the poor solvent, the ratio of the volume of the component (1) to the volume of the component (2) is 1 / 4 to 10 / 1; the ratio of the volume of the component (1) to the total volume of the component (2) and the component (3) is 1 / 10 to 1 / 2; A coating liquid, wherein the ratio of the volume of the component (4) to the volume of the component (3) is 1 / 1 to 100 / 1.

2. The major axis of the irregular shaped particles is 0.1 to 100 μm, The minor axis of the irregular shaped particles is 0.01 to 10 μm, 2. The coating liquid according to claim 1, wherein a ratio of a major axis of said irregular-shaped particles to a minor axis of said irregular-shaped particles is 2.0 or more.

3. The coating liquid according to claim 1 , wherein the poor solvent has a fluorine group.

4. 2. The coating liquid according to claim 1, wherein the poor solvent has a boiling point of 200° C. or lower under atmospheric pressure.

5. 2. The coating liquid according to claim 1, wherein the poor solvent has a surface tension of 22 mN / m or less.

6. the irregularly shaped particles are surface-modified with a silane coupling agent having a (meth)acryloyl group, 2. The coating liquid according to claim 1, wherein the difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer is 5 or less.

7. A method for forming protrusions, comprising the following steps [1] to [3]: [1] A step of applying the coating liquid according to any one of claims 1 to 6 to a supporting substrate to form a coating film. [2] A step of volatilizing the good solvent from the coating film to insolubilize the polymer [3] A step of volatilizing the poor solvent from the coating film in which the polymer has been insolubilized.

Citation Information

Patent Citations

  • Reflection preventing article

    JP2008209540A

  • Biomolecule extraction chip and method for manufacturing biomolecule extraction chip

    JP6606786B2